4 - Cheikh Anta Diop et le matérialisme historique: by Thierno Diop - Thierno Diop (Africa Development, 1998)
This paper deals with Cheikh Anta Diop's critique of historical materialism. It analyses works in which Diop expresses his agreements or disagreements with Marx's thesis concerning the role of physical living conditions as determined by the geographical milieu in primitive human societies. It also discusses the issue of revolutions. According to the author, the questioning of principles of Marxism allowed Diop to clear up the mystery surrounding black civilisation, hitherto considered as footnote to history, and also provided impetus for African marxists to study the continent's history.